High Burden of Vitamin B12 Deficiency among Adults and Elderly - Gyawali, Pratiksha; Bhatt, Rajendra Dev; Karmacharya, Robin Man; Pant, Vivek; Khadka, Ayesha (Journal of Nepal Health Research Council, 2023)
Background: Deficiency of vitamin-B12 is widespread. Adults and the elderly are particularly susceptible to vitamin-B12 deficiency. This study investigated the burden of vitamin-B12 deficiency and insufficiency among adults and the elderly attending a tertiary care hospital in Nepal. Methods: This is a retrospective chart review conducted at Dhulikhel hospital. We reviewed records of 1615 patients investigating Vitamin-B12 level (pmol/L) at the clinical biochemistry laboratory from laboratory management database MIDAS between June 2020 and December 2021. Vitamin-B12 level was measured using enzyme immunoassay in Abbott Architect i1000SR analyzer. The categorical variables are presented as frequency and percentage; and numerical variables as  means and standard deviations, or median and Interquartile range.  Pearson Chi-square test was used to determine association between categorical variables.  Mann Whitney test and Kruskal Wallis H test were used to compare Vitamin-B12 level by categories.Results: There were 1454 participants of which 33.5% of the patients were deficient, 27.9% were borderline deficient, while 38.7% had adequate vitamin B12 levels. Young adults(170.4 pmol/L) had a lower median vitamin B12 level than middle-aged adults (183.7pmol/L) and the elderly population (247.9pmol/L) (P<0.001). Compared to females (186.7 pmol/L), males(171.9 pmol/L) had lower vitamin B12 level (P <0.05).Conclusions: The study revealed that a significant proportion of young adults, middle aged adults and elderly population visiting a tertiary care hospital of Nepal are having vitamin B12 deficiency and borderline deficiency of public health concern. Keywords: Adults; deficiency; elderly, vitamin B12.